Retracted: Cardiovascular safety of oral antidiabetic therapy in type 2 diabetes mellitus- review article - Singh, P. S.; Yadav, Sudhir K.; Sharma, Himanshu; Kumar, Manoj (International Journal of Research in Medical Sciences, 2017)
The article titled “Cardiovascular safety of oral antidiabetic therapy in type 2 diabetes mellitus- review article” by Singh PS et al., published in International Journal of Research in Medical Sciences 2017;5(5):1742-1750, DOI: http://dx.doi.org/10.18203/2320-6012.ijrms20171805 is retracted. After the publication of the above article, one of the authors reported that some part of the text is plagiarized from his similar article published in Cardiovascular Diabetology, Volume 16 (2017), DOI: https://doi.org/10.1186/s12933-017-0499-5 (Xu J, Rajaratnam R. Cardiovascular safety of non-insulin pharmacotherapy for type 2 diabetes. Cardiovasc Diabetol. 2017 Feb 2;16(1):18. We contacted the author who could not satisfactorily respond to our queries. Since the author could not satisfactorily defend his article and contravened the declaration he made while submitting his manuscript, it was decided to retract the article from International Journal of Research in Medical Sciences and not to consider any manuscript submitted by him in future.